CODING UNPLUGGED SEBAGAI INOVASI PEMBELAJARAN UNTUK MEMBANGUN LITERASI DIGITAL ANAK USIA DINI DI PAUD - Widiastutik, Erna; Renandra, Irninda; Yayuk, Erna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of coding unplugged as an innovative learning approach to develop digital literacy among early childhood learners at TK Aisyiyah Cakru, Jember. This research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The coding unplugged activities were conducted in two sessions—“Walking to a Friend’s House” and “Coloring According to Code”—designed to stimulate children’s ability to follow instructions, organize sequences, and recognize symbolic patterns as the foundation of computational thinking. Data were analyzed interactively following the model of Miles, Huberman, and Saldana, which includes data reduction, data display, and conclusion drawing. The results revealed that coding unplugged served as an effective learning innovation to enhance children’s digital literacy. Children became more enthusiastic, independent, and capable of understanding sequencing, pattern recognition, and logical problem-solving. These findings reinforce the constructivist pedagogy and guided play approach as creative strategies to foster digital literacy from an early age.